2020
DOI: 10.1186/s13063-020-04645-z
|View full text |Cite
|
Sign up to set email alerts
|

Multi-centre, three arm, randomized controlled trial on the use of methylprednisolone and unfractionated heparin in critically ill ventilated patients with pneumonia from SARS-CoV-2 infection: A structured summary of a study protocol for a randomised controlled trial

Abstract: Objectives: To assess the hypothesis that an adjunctive therapy with methylprednisolone and unfractionated heparin (UFH) or with methylprednisolone and low molecular weight heparin (LMWH) are more effective in reducing any-cause mortality in critically-ill ventilated patients with pneumonia from SARS-CoV-2 infection compared to LMWH alone. Trial design: The study is designed as a multi-centre, interventional, parallel group, superiority, randomized, investigator sponsored, three arms study. Patients, who satis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Accordingly, both of these treatments seem to show a positive effect on the prognosis of COVID-19 patients, especially in the severe form of the disease with lungs involvement but, at present, no studies are available on the effectiveness of the LMWH associated with corticosteroids in the management of SARS-CoV-2 infection, compared to the single treatment administration. Simultaneous combined treatment with corticosteroid plus anticoagulant is under evaluation in only one trial [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Accordingly, both of these treatments seem to show a positive effect on the prognosis of COVID-19 patients, especially in the severe form of the disease with lungs involvement but, at present, no studies are available on the effectiveness of the LMWH associated with corticosteroids in the management of SARS-CoV-2 infection, compared to the single treatment administration. Simultaneous combined treatment with corticosteroid plus anticoagulant is under evaluation in only one trial [28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, current trials also showed the improvement of clinical outcomes due to the administration of corticosteroids in critical patients [22][23][24][25][26][27]. However, in viral COVID-19 pneumonia patients, data on the associated and simultaneous treatment with corticosteroids plus anticoagulant are still under evaluation [28].…”
Section: Introductionmentioning
confidence: 99%
“…Severe acute respiratory syndrome, which occurs in the most severe cases of COVID-19, sometimes cannot be avoided because mechanical ventilation is required to help patients breathe. This is another cause for concern because more than 70% of hospitalized patients whose condition requires mechanical ventilation, due to some other respiratory pathology, suffer from cognitive damage, mainly their ability to concentrate, their memory and their verbal fluency, and this even up to a year after being discharged (Busani et al, 2020;Sommer and Bakker, 2020).…”
Section: Ace2 In Brain Expression and Activitymentioning
confidence: 99%
“…This review aim to contribute with additional information that may be applied in the futures randomized‐controlled trails (RCT) on COVID‐19 treatment, based on our experience with similar pathological findings of microthrombosis in cutaneous blood vessels found in patients with livedoid vasculopathy. Unfortunately, a systematic review including RCT for COVID‐19 treatment with anticoagulation (warfarin, heparin or new direct oral anticoagulants) and/or HBOT were not showed published results disposable until September 23, 2020, as demonstrated in Table 1 15,29,37‐43 …”
Section: Anticoagulationmentioning
confidence: 99%